Dataset1 Femtosecond fiber Bragg grating fabrication with adaptive optics aberration compensation - Salter, P; Woolley, M; Morris, S; Booth, M; Fells, J (University of Oxford, 2019)
Underlying data for Patrick S. Salter, Matthew J. Woolley, Stephen M. Morris, Martin J. Booth, and Julian A. J. Fells, "Femtosecond fiber Bragg grating fabrication with adaptive optics aberration compensation," Opt. Lett. 43, 5993-5996 (2018)